Surface-Modified Carbon Dots for Cancer Therapy: Integrating Diagnostic and Therapeutic Applications - González M; Romero MP (International Journal of Nanomedicine, 2025)
Myriam González, Maria P Romero Escuela Politécnica Nacional, Departamento de Materiales, Quito, 170143, EcuadorCorrespondence: Maria P Romero, Escuela Politécnica Nacional, Departamento de Materiales, Quito, 170143, Ecuador, Email maria.romerom@epn.edu.ecAbstract: Carbon dots (CDs) have become versatile nanomaterials that have found practical applications in cancer therapy due to their small size, tunable photoluminescence, and high biocompatibility. Modified CDs have shown remarkable potential in targeted drug delivery systems, enhancing solubility and specificity in tumor sites while minimizing systemic toxicity. Gene therapy applications take advantage of the ability of CDs to condense and protect genetic material from degradation, thereby facilitating efficient cellular uptake. Furthermore, metal-doped CDs can function as fluorophores and enhance imaging capabilities for tumor detection through fluorescence and MRI. Besides, in phototherapy applications, when combining photodynamic (PDT) and photothermal therapy (PTT), CDs exhibit synergistic effects wherein therapeutic efficacy is increased by the generation of reactive oxygen species (ROS) and heat. This review summarizes recent developments in surface-modified and doped CDs for in vitro and in vivo applications, particularly in drug delivery, gene therapy, multimodal imaging, photodynamic therapy (PDT), photothermal therapy (PTT), chemodynamic therapy (CDT), sonodynamic therapy (SDT) and gas therapy, for cancer therapies. Advances in modalities of surface modification that include ligand binding and metal doping have significantly improved CDs’ biocompatibility and targeting precision. However, limitations such as low drug-loading capacity, complex synthesis processes, and the challenges created by hypoxic tumor environments need to be opened for further research. Future directions will focus on enhancing drug-loading efficiency, establishing long-term biocompatibility, and optimizing multifunctional nanocomposite designs for integrated cancer therapies.Keywords: carbon dots, cancer therapy, nanocarrier system, photodynamic therapy, photothermal therapy, chemodynamic therapy, sonodynamic therapy